Different Instructional Methods In Arabic: Measuring Their Impact On Students' Writing Skill - Munawaroh, Imroatul; Ilham Nur Kholiq (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study investigates the impact of varying instructions in Arabic language learning on improving students' writing skills. Using a quasi-experimental method with a one-group pretest-posttest design, this study involved 30 madrasah diniyah students in Hidayatun Nasyi'in Islamic boarding school. The research instruments consisted of a questionnaire containing 20 items and a writing skills test covering pretest and posttest. Data analysis was performed using descriptive statistics, Shapiro-Wilk and Kolmogorov-Smirnov normality tests, and paired T-tests. The results showed a significant increase between the pretest (Mean=69.47, SD=10.28) and posttest (Mean=84.33, SD=8.37) scores with a t(29) = -10.631 and p = 0.000, and all instruments were proven to be valid (r > 0.361, p < 0.05) with a Cronbach's Alpha reliability coefficient of 0.744. These findings underscore the effectiveness of the differentiated approach in teaching Arabic writing tailored to students' ability levels, as well as the relevance of cognitive load theory in the teaching context. This study recommends the application of varied instruction to increase student engagement and understanding in the Arabic language learning process.